Pengambilalihan Agunan Kredit Macet oleh Bank Perkreditan Rakyat - Ida Ayu Padma Trisna Dewi; Anak Agung Gede Duwira Hadi Santosa (University of Udayana, 2023)
This paper aims to provide the understanding and knowledge of the takeover of an non performing loan collaterals by Rural Banks through auctions after the Constitutional Court Decision Number 102/PPU-XVIII/2020. This paper uses a normative legal research type and examines the arrangements for conducting auctions and taking over bad credit collateral by BPR after the Constitutional Court's decision Number 102/PUU-XVIII/2020 using the Statue Approach and the Conceptual Approach. The results of this study conclude that the submission of a judicial review of Article 12A paragraph (1) of the Banking Law by PT. BPR Lestari Bali is inseparable fromithe existence of the